Some important characteristics of asset bubbles and financial crises - Yip, Paul Sau Leung (2021)
This paper first discusses the major characteristics of the seeding stage, the development stage and the final stage of an asset bubble. In particular, it emphasizes the role of expectation, some major changes in economic behaviors, financial leveraging, some important vicious cycles, upward spirals and herding behavior in the eventual development of an asset bubble. Thereafter, it discusses the policy implications of such an analysis. The second half of the paper extends the discussion to some important changes in economic behaviors, financial deleveraging, vicious cycles and downward spirals that would push an early-developed financial crisis into a full-blown economic crisis. Based on the characteristics and the experience of some major financial crises in the past few decades, the paper discusses policy measures that could be adopted during the crisis period and the post-crisis recession.